Tax Digital Management, Human Resource Competencies, and Entrepreneurial Resilience in the Industry 4.0 Era - Deddy Dariansyah; Ryan Firdiansyah Suryawan (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to partially and simultaneously analyze the influence of Digital Tax Management (X?) and Human Resource (HR) Competencies (X?) on Entrepreneurial Resilience (Y) among MSMEs in Indonesia during the Industry 4.0 era. Research Methodology: A quantitative approach was employed using a cross-sectional survey of 100 MSME actors who have adopted digital tax systems and technology-based HR tools. Data were collected via questionnaires and analyzed using multiple linear regression, t-tests, F-tests, and classical assumption tests with SPSS 24. Results: Digital Tax Management significantly influences Entrepreneurial Resilience (t = 4.868 > 1.985; p = 0.000 < 0.05). Human Resource Competencies also show a significant effect (t = 5.671 > 1.985; p = 0.000 < 0.05). Simultaneously, both variables contribute 70% to Entrepreneurial Resilience (R² = 0.700; F = 112.790 > 3.09; p = 0.000). Conclusions: This study highlights that Digital Tax Management and HR Competencies significantly enhance Entrepreneurial Resilience among MSMEs in Indonesia. Digital tax systems improve compliance and efficiency, while HR competencies in digital skills help businesses adapt and thrive in the face of challenges, together accounting for a significant portion of Entrepreneurial Resilience. Limitations: The study is limited to the implementation of digital tax systems and technology-based HR competency development, with HR competencies showing a more dominant influence. Contributions: The findings encourage MSMEs to strengthen their use of digital tax services and HR tech skills, while urging the government to broaden outreach and training to ensure inclusive digital transformation for all MSME levels.